IMPLIKASI CORPORATE GOVERNANCE DAN GENDER DIVERSITY TERHADAP KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR NON-KEUANGAN DI INDONESIA - Intan Monica Hanmastiana; Harjum Muharam (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the implications of corporate governance and gender diversity on financial distress conditions. Corporate governance variables are projected using institutional ownership, family ownership, foreign ownership, blockholder's ownership, and board size. Then, gender diversity variables are projected using the gender diversity of the board of commissioners and the gender diversity of the board of directors. The study also added leverage and firm size as control variables. In order to expand the scope of the previous research, a comparative analysis of the company's financial distress conditions before and during the COVID-19 pandemic was added. This study used a purposive sampling technique, where a total sample of 207 non-financial sector companies listed on the Indonesia Stock Exchange (IDX) was obtained consecutively during the observation period, namely 2017-2021. The research data is sourced from the annual report published through the official website of the Indonesia Stock Exchange and the company's official website. The analysis method used is logistic regression analysis and comparative tests using Wilcoxon Signed Rank Test. This study provides findings that institutional ownership, family ownership, foreign ownership, board size, gender diversity of the board of commissioners, and variable control leverage and firm size have a negative and significant effect on financial distress. However, the blockholder's ownership and gender diversity of the board of directors did not show a significant effect on financial distress. Then, the results of comparative tests proved that there was a significant difference between the condition of financial distress before and during the COVID-19 pandemic.